2012
DOI: 10.4172/2155-9546.1000141
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Tilapia Culture in Watershed Pond in Bangladesh

Abstract: With a view to assess the suitability of mono-sex Tilapia (Oreochromis niloticus) culture using downstream flow from hills by observing their growth, survival and production in watershed pond, an experiment was carried out in a commercial aquaculture farm Mrittika Fisheries, Odolia, Hathazary, Chittagong. The duration of {each} culture period was 4 months. Stocking densities of the three culture ponds were same as, 10 individuals/m 2. All the fish were of same age group having mean body weight about 1.2 gm. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Moreover, such culture of tilapia is more profitable for mono-sex than mixed-sex operations. A study conducted by Rahman et al (2012) demonstrated a 78.11% profit from mono-sex tilapia over mixed-sex tilapia in watershed ponds during the summer season in Bangladesh. In conclusion, it is possible to successfully culture mixed-sex and mono-sex tilapia during the winter period and the growth of mono-sex tilapia is significantly better (32%) than that of mixed-sex tilapia cultured in over-wintered experimental ponds.…”
Section: Fig 1 Growth Patterns In Terms Of Weight and Length Gain Ovmentioning
confidence: 99%
“…Moreover, such culture of tilapia is more profitable for mono-sex than mixed-sex operations. A study conducted by Rahman et al (2012) demonstrated a 78.11% profit from mono-sex tilapia over mixed-sex tilapia in watershed ponds during the summer season in Bangladesh. In conclusion, it is possible to successfully culture mixed-sex and mono-sex tilapia during the winter period and the growth of mono-sex tilapia is significantly better (32%) than that of mixed-sex tilapia cultured in over-wintered experimental ponds.…”
Section: Fig 1 Growth Patterns In Terms Of Weight and Length Gain Ovmentioning
confidence: 99%
“…The cultural period and rearing seasonal periods along with factors can make the difference in production in the pond. The difference between net returns of GIFT tilapia and IMC was 160% more than of IMC net profit (Rahman et al, 2012) [43] . As per the statement by (De et al, 2012, Rahman et al, 2012 [62,43] that intensive Carp and Tilapia culture feed was the highest cost item.…”
Section: Cost Benefit Analysis (Cba)mentioning
confidence: 99%
“…The difference between net returns of GIFT tilapia and IMC was 160% more than of IMC net profit (Rahman et al, 2012) [43] . As per the statement by (De et al, 2012, Rahman et al, 2012 [62,43] that intensive Carp and Tilapia culture feed was the highest cost item. In the present study the similar kind of observation found in both GIFT tilapia and IMC poly-culture.…”
Section: Cost Benefit Analysis (Cba)mentioning
confidence: 99%
“…Among the progressive cultured species of fishes, tilapia is comparatively popular, which is produced and consumed widely in Asian countries (Prabu et al, 2019). In Bangladesh, tilapia species were first introduced from Thailand in 1954 (Rahman et al, 2012). The culture of these species helps a huge community in terms of livelihood, raises their income, and helps in mitigation of poverty.…”
Section: Introductionmentioning
confidence: 99%